2023
DOI: 10.9778/cmajo.20220188
|View full text |Cite
|
Sign up to set email alerts
|

The impact of delayed nonurgent surgery during the COVID-19 pandemic on surgeons in Alberta: a qualitative interview study

Abstract: Background: During the COVID-19 pandemic, nonurgent surgeries were delayed to preserve capacity for patients admitted with COVID-19; surgeons were challenged personally and professionally during this time. We aimed to describe the impact of delays to nonurgent surgeries during the COVID-19 pandemic from the surgeons’ perspective in Alberta. Methods: We conducted an interpretive description qualitative study in Alberta from January to March 2022. We recruited adult and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…7,8 The distress of delaying nonurgent surgeries extended to surgeons who worried about their patients' health, had to shift responsibilities away from surgery to help with the COVID-19 response, the consequences of which extended into their personal lives. 9 There were also wider impacts of the COVID-19 response; it has been reported that there has been an excessive death rate (beyond COVID-19 cases) in several health conditions some of which may be directly related to delayed surgeries, [10][11][12] and fewer patients sought medical care for fear of contracting COVID-19 in healthcare settings which is likely to have a trickle-down effect for some time. 13,14 Despite all that is now known about the impact of the COVID-19 response, during the height of COVID-19 little evidence was available to support decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The distress of delaying nonurgent surgeries extended to surgeons who worried about their patients' health, had to shift responsibilities away from surgery to help with the COVID-19 response, the consequences of which extended into their personal lives. 9 There were also wider impacts of the COVID-19 response; it has been reported that there has been an excessive death rate (beyond COVID-19 cases) in several health conditions some of which may be directly related to delayed surgeries, [10][11][12] and fewer patients sought medical care for fear of contracting COVID-19 in healthcare settings which is likely to have a trickle-down effect for some time. 13,14 Despite all that is now known about the impact of the COVID-19 response, during the height of COVID-19 little evidence was available to support decision-making.…”
Section: Introductionmentioning
confidence: 99%